Relational coaching : journeys towards mastering one-to-one learning - Haan, Erik de.; Stewart, Sue. (Chichester, England ; Hoboken, N.J. : J. Wiley, 2008)
Coaching has had a face-lift in recent years. It has gone from being a last resort, something that only happened when things were going wrong, to affording status.
pt. I. The ways of coaching -- Introduction: the paths towards coaching -- 1. From intake to intervention: the outlines of a profession -- 2. From stigma to status: the growth of a profession -- 3. From prize-fighting to prizes for all: the active ingredients -- 4. From intervention to interaction: relational coaching -- pt. II. The ways of research -- Introduction: the paths towards research -- 5. Coachees have their say: which interventions work for us? -- 6. 'I doubt therefore I coach': critical moments of less experienced coaches -- 7. 'I struggle and emerge': critical moments of experienced coaches -- 8. Coaches have their say: how to handle critical moments? -- pt. III. The ways or excellence -- Introduction: the paths towards excellence -- 9. Training and accreditation of the executive coach -- 10. Continuing professional development of the executive coach -- 11. Library of the executive coach -- 12. Future of the executive coach -- App. A. 80 critical moments of new coaches -- App. B. 78 critical moments of experienced coaches -- App. C. Case study: Tamara -- App. D. Verbatim transcript: Ken -- App. E. Code of conduct for executive coaches -- App. F. Intake instruments and checklists.
Title from title screen.
Includes bibliographical references.
John Wiley and Sons
Keywords: Executive coaching; Employees -- Coaching of; Personal coaching; Accompagnement de gestionnaires; Accompagnement (Psychologie); Employees -- Coaching of; Executive coaching; Personal coaching; Coaching